Anxiety of speaking English in class among international students in a Malaysian university - Zhiping, Diao; Paramasivam, Shamala (Contemporary Research Centre, 2013)
The study investigates the reasons international students’ suffer anxiety and explore how they cope with their fear and anxiety when speaking English in class. The study also examines teachers’ perspectives and reactions towards learners’ anxiety and investigates the students’ perspectives of teachers’ reaction to their feelings of anxiety. Horwitz’s et.al (1986) categorization of variables that lead to foreign and second language anxiety is used as the theoretical framework. Data collection involves observations and interviews of 8 international postgraduate students of a Malaysian university and data was analyzed through discourse analysis. Findings indicate that Nigerians generally are not anxious of speaking. Differently, Iranians and Algerians suffer more from anxiety as a result of fearing negative evaluation and communication apprehension. The conclusions point out that the lecturers’ strategies and students’ reactions to their strategies are not related to cultural backgrounds but to affective filters and learning skills common to all human beings.